Lower Cambrian trilobites from North Greenland - Blaker, Mark R.; Peel, John S. (Meddelelser om Grønland. Geoscience, 1997)
Fifty five trilobite species are described from Lower Cambrian platform margin to outer shelf deposits of North Greenland. The species indicate the "Nevadella" and Olenellus Zones of the North American standard, equivalent to uppermost Atdabanian(?), Botomian and Toyonian of Siberian usage. Basal siliciclastic sediments of the Buen Formation yield a Buenellus higginsi fauna ("Nevadella" Zone), including the exceptionally preserved fossils of the Sirius Passet fauna. A Limniphacos perspicullum and Olenellus hyperboreus fauna indicates the "Nevadella" and Olenellus zonal boundary while uppermost beds contain O. svalbardensis and Alacephalus? davisi (Olenellus Zone). Carbonate and siliciclastic sediments of the overlying Brønlund Fjord Group yield trilobites of the upper Olenellus Zone. The Kap Troedsson and Aftenstjernesø Formations contain Ekwipagetia marginata, Serrodiscus spp. and Calodiscus lobatus. Species of Kootenia, Ogygopsis, Zacanthopsis, Perissopyge, Pagetides and Bonnia are conspicuous from the Henson Gletscher Formation, together with Peronopsis roddyi. Oryctocephalids such as Arthricocephalus chauveaui and Halikoplanktos jishouensis allow correlation with the Megapalaeonus Zone of China and are also recognised in Siberia. The Sæterdal Formation contains olenelloids, Kootenia marcoui, and Bonnia brennus. New genera: Limniphacos, Haliplanktos. New species: Limniphacos perspicullum. Kootenia oscari, K. radiata, K. sagena.